IMPROVING THE INFRASTRUCTURAL SUPPORT SYSTEM OF SMALL BUSINESS ENTITIES (Scientific electronic journal "Labor Economics and Human Capital", 2024)
This paper proves that infrastructure factors should be taken into account in the effective organization of the state support system for small business entities. Paper focuses on the infrastructural support of the activities of small business entities, which regulates and authorizes the operations of the economic entities and the infrastructure complex, as a continuous process of implementation of management functions, ensures the distribution and redistribution of resources in them, and achieves positive results for the public and private sectors. As a result of the study, a mechanism for improving the state infrastructural support system for the activities of small business entities was proposed.
Keywords: small business entities, state support, infrastructural support of small business activities